Comparison on the Effects and Safety of Tualang Honey and Tribestan in Sperm Parameters, Erectile Function, and Hormonal Profiles among Oligospermic Males - Ismail, Shaiful Bahari; Bakar, Mohd. Bustamanizan; Nik Hussain, Nik Hazlina; Mohd Noor, Norhayati; Sulaiman, Siti Amrah; Jaafar, Hasnan; Draman, Samsul; Ramli, Roszaman; Wan Yusoff, Wan Zahanim (Hindawi Publishing Corporation, 2014)
This study aims to evaluate the effectiveness of Tualang honey on sperm parameters, erectile function, and hormonal and safety profiles. Methodology. A randomized control trial was done using Tualang honey (20 grams) and Tribestan (750mg) over a period of 12 weeks. Sperm parameters including sperm concentration, motility, and morphology were analyzed and erectile function was assessed using IIEF-5 questionnaire. Hormonal profiles of testosterone, FSH, and LH were studied. The volunteers were randomized into two groups and the outcomes were analyzed using SPSS version 18. Results. A total of 66 participants were involved. A significant increment of mean sperm concentration (